Self-Acceprance of Parents Who Have Children With Special Needs at Benpasi State Special School - Kuabib, Theresa Sandra; ,, Marni; Mage, Mernon Yerlinda Carlista (Journal of Health and Behavioral Science, 2024)
Children with special needs are children with mental, intellectual, physical, behavioral, emotional and communication limitations which can have an impact on the child's growth and development, making them different from other children their age. The importance of self-acceptance by parents of ABK in order to optimize the potential and development of ABK through the stages of acceptance according to Germer (2009), namely: Aversion, Curiosity, Tolerance, Allowing, Friendship. This research aims to describe the self-acceptance process of parents who have ABK at SLBN Benpasi. The research design uses a qualitative research approach with phenomenology with 5 subjects based on criteria determined using a purposive sampling technique. The data collected was analyzed using hermeneutic phenomenological analysis techniques and produced 3 main themes, namely, the challenge of acceptance, the process of facing reality, and coming to terms with reality. The process of self-acceptance by ABK parents experienced a positive acceptance process. Each participant was successful and able to go through each process well in different ways.